ANALYSIS OF STUDENTS’ PROFICIENCY ON ENGLISH PRONUNCIATION USING YOUTUBE-BASED VIDEO MEDIA - Mulyani; Dewi Sartika (English Education Department, 2019)
Pronunciation is a fundamental element in English required by students in order to succeed in speaking and writing. From preliminary studies, preliminary information wasobtained that the ability of students’pronunciation in English is still low and that they often have difficulty in pronouncing vocabulary is another problem faced in schools both by students and teachers. If students cannot pronounce vocabulary clearly and precisely, it might cause misunderstandings so that it is possibly bother both written and oral communication with other speakers. Other problems are the selection of media and learning methods that are not appropriate. Based on the results of current research, English pronunciation learning through an effective media and up-to-date approach can improve students' abilities so that these problems need to be addressed. Therefore, the use of YouTube-based video media is strongly believed to improve students' pronunciation skills. Learning English with appropriate methods in order to improve students 'pronunciation skills is highly needed so that teachers are expected to be able to provide enjoyable learning experiences through YouTube-based media with appropriate methods so that students' pronunciation skills improve. This study aims at providing an alternative teaching of English pronunciation skills for students in junior high school through the use of YouTube-based video media with relevant activities. This research was conducted using a mixed method approach; quantitative in the form of quasi-experimental and qualitative. Quantitative data sources from the pre-test and post-test conducted to find out whether the use of YouTube-based video media can improve the pronunciation of the eighth year students of SMP 2Mesjid Raya or not. In addition, qualitative data is also needed as a clarification of test results derived from field notesand interview. The results of the study indicate that there is a significant improvement from pre-test to post-test on students' ability in English pronunciation through the use of YouTube-based video media where the Sig or P Value is 0,000 <0.05.